Pengaruh Penggunaan Media Gambar Berseri Terhadap Kemampuan Menulis Karangan Narasi Cerita Pendek Siswa Kelas IV Gugus VIII Kota Bengkulu - Maftuchoh, Joana; Yuliantini, Nani; Anggraini, Dwi (JURIDIKDAS, 2025)
This research aims to determine the effect of serial image media using on the ability to write a short story narrative essays for fourth grade students of cluster VIII Bengkulu City. Research was quantitative research and the method was a quasi-experimental method with The Matching Only Pretest-Posttest Control Group Design. The population in this study was SDN Cluster VIII Bengkulu City. The samples were students of grade IV of SDN 36 Bengkulu City as the experimental group using serial image media and students of grade IV of SDN 18 Bengkulu City as the control group using ordinary image media. The research instrument was a test in the form of description questions. The data analysis were descriptive analysis, prerequisite test, and inferential analysis, called t-test. The result of this research showed a significant difference between the posttest mean scores of experimental and control group. These result were proved by value of the table distribution based on df = 46 with a degree of significance α = 0,05 is 1,679. So, the value of tcount > ttable (4,368 > 1,679) and sig, (2-tailed) of 0,001 < 0,05. Then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an significant effect of serial image media using on the ability to write short story narrative essays for fourth grade students of cluster VIII of Bengkulu City.